Identification of biofilm-forming Escherichia coli in dressed chickens from a selected slaughterhouse in Calamba City, Laguna - Santamaria, Janyll Helaena D.; Talagtag, Maxine E.; Ventanilla, Yuan L.; Zialcita, Althea Brianna O.
Background E. coli is known for its role in propagating antimicrobial resistance (AMR) and its biofilm-forming capability. AMR is one of the top global public health challenges of the 21st century. Apart from the clinical setting, AMR within the agricultural sector is relevant due to the risk of persistent infections in humans and animals. Biofilm formation, a bacterial survival mechanism, contributes to AMR primarily through recalcitrance and horizontal gene transfer. There is, however, a lack of research investigating biofilm formation among broiler chickens at the slaughterhouse level. This study aimed to investigate the presence, the antimicrobial susceptibility profile, and the biofilm-forming capability of E. coli from broiler chickens in a selected slaughterhouse from Calamba City, Laguna.